Sustainable well-being: an empirical exploration on human needs and human interdependency - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2016)
This study is a part of an ongoing research to discover subjective indicators of sustainable well-being for Malaysia. Initial findings recognized two important notions of subjective measures of sustainable well-being. The first notion suggested that sustainable well-being manifested in human interdependency. The second notion suggested that human interdependency is attained when human needs are fulfilled. Maslow’s Hierarchy of Needs was adopted to indicate the stages and examples of each needs. There were eight stages of human needs which were adapted into 24 common human needs substituted under eight components of three human needs dimensions. The dimensions were (i) basic necessities, (ii) complimentary needs, and (iii) desired opportunities. It was hypothesized that human needs influence the level of human interdependency. This paper delivers an empirical analysis testing the effects of human needs on human interdependency. The study intends to determine the influence of human needs on human interdependency. Questionnaire survey was conducted and 894 reliable samples were gathered. 192 Independent Sample T-Tests were conducted to determine statistical difference in levels of eight components of human interdependency, between respondents who claimed difficult and respondents who claimed easy to attain 24 human needs in the past year. There were statistically significant differences in most of the components of human interdependency between groups of 24 human needs. The empirical study conducted in the central regions of a developing and multicultural country, Malaysia, is a useful reference to subjective well-being studies piloted in areas of similar characteristics.